Vincular palabra y la realidad: un trabajo por hacer: Reseña de La Bastarda (2016) de Trifonía Melibea Obono (Periphērica, 2024)
This is a review of the Equatoguinean novel La Bastarda de Trifonía Melibea Obono published by Flores Raras in 2016. The review includes comments related to the content, style and merit of the work as an example of feminist literature and in defense of human rights to gender diversity. In essence it argues that the novel is reminder of the relationship between words and reality underlining the need to recognize and name homosexuality in Fang culture in order to grant social (and eventually legal) respect and dignity to divergent sexualities. In addition, the review points out some perspectives on the existing debate about the indigeneity of homosexuality in the post-colonial African context.